Management Support as the Dominant Driver of Occupational Health and Safety Compliance Among Hospital Security Personnel - Kurnia Dwi Cahya Rose; Joko Suyono (International Journal of Industrial Engineering, Technology & Operations Management, 2025)
Occupational Health and Safety (OHS) compliance is essential to ensuring workplace safety in healthcare environments, yet research has predominantly focused on medical personnel, with limited attention to non-medical staff, such as hospital security officers. These personnel face unique occupational risks, including exposure to emergencies and workplace conflicts, making compliance with safety procedures critically important. This study aims to examine the influence of OHS training, supervision, availability of safety facilities, and management support on the compliance behavior of hospital security officers. A quantitative explanatory design with a cross-sectional approach was employed, involving all 30 security officers in a regional public hospital in Surabaya, Indonesia, using a total sampling technique. Data were collected through structured questionnaires and analyzed using multiple linear regression. The findings reveal that OHS training and management support have a positive, statistically significant effect on compliance, whereas supervision and the availability of safety facilities do not. The model demonstrates strong explanatory power, indicating that organizational factors collectively influence compliance behavior. Notably, management support emerges as the most dominant factor, highlighting the critical role of leadership commitment in fostering a safety-oriented work environment. The study concludes that improving compliance among hospital security personnel requires an integrated approach that prioritizes strong managerial support and continuous training, alongside improvements in supervision and effective utilization of safety facilities.